2015
DOI: 10.1002/lt.24059
|View full text |Cite
|
Sign up to set email alerts
|

CD47 blockade reduces ischemia/reperfusion injury and improves survival in a rat liver transplantation model

Abstract: Orthotopic liver transplantation (OLT) remains the standard treatment option for nonresponsive liver failure. Because ischemia/reperfusion injury (IRI) is an important impediment to the success of OLT, new therapeutic strategies are needed to reduce IRI. We investigated whether blocking the CD47/thrombospondin-1 inhibitory action on nitric oxide signaling with a monoclonal antibody specific to CD47 (CD47mAb400) would reduce IRI in liver grafts. Syngeneic OLT was performed with Lewis rats. Control immunoglobuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 42 publications
(69 reference statements)
1
36
0
1
Order By: Relevance
“…In liver and kidney I/R models, CD47 knockout mice were found to suffer less damage compared to control mice after periods of vascular occlusion followed by recanalization [13,17]. Administration of the CD47 monoclonal antibody similarly improved the survival of ischemic skin flaps and skin grafts, and both liver and kidney mouse I/R models [14,15,38,39].…”
Section: Down-regulation Of Cd47 Attenuates I/r Induced Oxidative Strmentioning
confidence: 88%
See 1 more Smart Citation
“…In liver and kidney I/R models, CD47 knockout mice were found to suffer less damage compared to control mice after periods of vascular occlusion followed by recanalization [13,17]. Administration of the CD47 monoclonal antibody similarly improved the survival of ischemic skin flaps and skin grafts, and both liver and kidney mouse I/R models [14,15,38,39].…”
Section: Down-regulation Of Cd47 Attenuates I/r Induced Oxidative Strmentioning
confidence: 88%
“…Bauer et al reported that both TSP1 and CD47 are significantly upregulated in vascular cells during states of ischemia [12]. Blocking of the TSP1/CD47 signal using an anti-CD47 monoclonal antibody (CD47 mAb) in wild-type mice, or by generation of CD-47 knock-out mice, can mitigate kidney, liver, and tissue flap damage and improve tissue survival in I/R models [13][14][15][16][17]. However, the physiological function of CD47 in MIRI has yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Caspase-3 is the effector protease in the apoptotic cascade. It plays a significant role in IR-induced liver injury [44]. There are many processes implicated in activation of caspase-3 including TNF-α/TNF receptor, Fas/Fas ligand interaction, oxygen-free radical generation and nuclear factor-κB activation [8,10].…”
Section: Discussionmentioning
confidence: 99%
“…Rats were fed a standard rat chow diet and tap water and left to acclimatize for one week before the experiment. The experiment was conducted with adherence to the ethical standards Life Sciences 134 (2015) [42][43][44][45][46][47][48] approved by the faculty board committee of the Faculty of Medicine, Minia University, Egypt and in accordance with The Code of Ethics of the World Medical Association (Declaration of Helsinki) for animal experiments.…”
Section: Animalsmentioning
confidence: 99%
“…Mice (217) and rats (140) treated with CD47 antibodies sustained less injury after syngeneic renal transplantation, and in rats this was associated with increased blood flow 24 h post-transplantation. In healthy and steatotic rat liver transplantation ischemia-reperfusion models, pretreatment with a CD47 antibody (mAb400) was associated with improved animal survival, less organ injury, and lower superoxide levels, as characterized by dihydroethidium fluorescence of liver tissue sections (303,304).…”
Section: Tsp1 and Ros Signaling In Vivomentioning
confidence: 99%